2019
DOI: 10.1159/000500453
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Adverse Perinatal Outcomes at Term Delivery Using Ultrasound Estimated Percentile Weight at 35 Weeks of Gestation: Comparison of Five Fetal Growth Standards

Abstract: <b><i>Objective:</i></b> To assess the predictive ability of the ultrasound estimated percentile weight (EPW) at 35 weeks of pregnancy to predict adverse perinatal outcomes (APOs) at term delivery according to 5 fetal growth standards, including population, population-customized, and international references. <b><i>Methods:</i></b> This was a retrospective cohort study of 9,585 singleton pregnancies. Maternal clinical characteristics, fetal ultrasound data obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…On the contrary, when we analyzed LGAs with the APO predictive ability of the 6 standards by percentile weight >90 at the 35th week of gestational age, customized Figueras and MSUH standards showed the greatest diagnostic ability, with statistically significant differences with 3 of the 4 NC models. A previous study did not find any significant difference between customized and NC standards analyzing the predictive ability of EPW to detect APOs; by contrast, using EPW >90, we detected significant differences [9]. The shorter ultrasound-delivery interval is related to better prediction rates with all the standards.…”
Section: Principal Findingscontrasting
confidence: 68%
See 1 more Smart Citation
“…On the contrary, when we analyzed LGAs with the APO predictive ability of the 6 standards by percentile weight >90 at the 35th week of gestational age, customized Figueras and MSUH standards showed the greatest diagnostic ability, with statistically significant differences with 3 of the 4 NC models. A previous study did not find any significant difference between customized and NC standards analyzing the predictive ability of EPW to detect APOs; by contrast, using EPW >90, we detected significant differences [9]. The shorter ultrasound-delivery interval is related to better prediction rates with all the standards.…”
Section: Principal Findingscontrasting
confidence: 68%
“…Since ultrasound assessment allows professionals to monitor intrauterine growth, different fetal growth standards have been based on the EFW to calculate the estimated percentile weight (EPW) using Hadlock et al’s [6, 7] methodology or more recent studies that apply multilevel models. Although studies such as the one conducted by Gardosi et al [8] have claimed that these standards can also be customized to maternal and fetal physiological variables, other studies have questioned the validity of customized standards [9, 10]. Moreover, international population standards have recently been published by EFW [11], including those from the INTERGROWTH-21st project [12, 13] and the World Health Organization (WHO) [14].…”
Section: Introductionmentioning
confidence: 99%
“…found that the association between birth‐weight percentile and adverse neonatal outcome was similar when customized or non‐customized birth‐weight or fetal growth standards were applied in nulliparous women. Similarly, others observed no improvements in the prediction of neonatal morbidity 58–60 and stillbirth 59,60 by customized fetal growth standards when compared to non‐customized charts. However, we have demonstrated recently that there was a modest benefit in the customized evaluation of fetal growth for prediction of perinatal mortality, yet the choice of the customized and non‐customized standards being compared can also have an effect 58 .…”
Section: Discussionmentioning
confidence: 98%
“…Small-for-gestational-age (SGA) infants-those with a birth weight below the 10th percentile-have been associated with increased risk of adverse perinatal outcomes [35,36]. Predicting them from the ultrasound percentile at the 35th gestational week as well as other fetal and parental variables may help to avoid these outcomes.…”
Section: Application To Real Datamentioning
confidence: 99%